Development of Photoelectric Effect Learning Media based on Arduino Uno - Hardi Hamzah; Dewi Sartika; Muhammad Nurkhalis Agriawan (Indonesian Review of Physics, 2022)
This study aims to develop a photoelectric effect learning media based on Arduino Uno. The subjects in this study were students who took Modern Physics courses. The media development procedure uses the Borg and Gall model, which is limited to seven stages. The feasibility of the developed media refers to the results of the media expert's assessment, the level of practicality, and the effectiveness of the media. The test results show that the product's Planck constant of 6.62 × 10-34 J.s corresponds to the theoretical value. Three experts concluded that the learning media had a good level of feasibility to be used as an experimental tool. The level of practicality and effectiveness of the media showed good results. That is, practical and effective media to be used in experiments. So, it can be concluded that the Arduino Uno-based photoelectric effect learning media that has been developed is suitable for use in learning.